2021
DOI: 10.1016/j.ijid.2021.07.063
|View full text |Cite
|
Sign up to set email alerts
|

Initial SARS-CoV-2 vaccination response can predict booster response for BNT162b2 but not for AZD1222

Abstract: Objectives : Our objective was to determine whether SARS-CoV-2 antibody levels after the first dose can predict the final antibody response and whether this is dependent on the vaccine type. Methods : 69 BNT162b2 (Pfizer/BioNTech) and 55 AZD1222 (AstraZeneca) vaccinees without previous infection or immunosuppressive medication were included. Anti-body levels were quantified 3 weeks after dose 1, in case of AZD1222 directly before boostering (11 weeks after dose 1) and 3… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
7
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 27 publications
3
7
1
Order By: Relevance
“…The humoral immune response after vaccination could differ according to age, gender, and ethnicity. This study demonstrated that age and gender did not statistically affect the antibody response after the second vaccination, and other previous studies showed conflicting results for vaccine response by age and gender ( 14 , 15 , 18 , 21 ). Moreover, the dosing interval of BNT162b2 is 3 to 4 weeks whereas that of ChAdOx1 nCoV-19 is 8 to 12 weeks to maximize the effect of the first vaccination ( https://www.gov.uk/government/publications/prioritising-the-first-covid19-vaccine-dose-jcvi-statement/optimising-the-covid-19-vaccination-program-for-maximum-short-termimpact ).…”
Section: Discussioncontrasting
confidence: 52%
See 1 more Smart Citation
“…The humoral immune response after vaccination could differ according to age, gender, and ethnicity. This study demonstrated that age and gender did not statistically affect the antibody response after the second vaccination, and other previous studies showed conflicting results for vaccine response by age and gender ( 14 , 15 , 18 , 21 ). Moreover, the dosing interval of BNT162b2 is 3 to 4 weeks whereas that of ChAdOx1 nCoV-19 is 8 to 12 weeks to maximize the effect of the first vaccination ( https://www.gov.uk/government/publications/prioritising-the-first-covid19-vaccine-dose-jcvi-statement/optimising-the-covid-19-vaccination-program-for-maximum-short-termimpact ).…”
Section: Discussioncontrasting
confidence: 52%
“…According to the previous study ( 15 ), BNT162b2 resulted in higher antibody values than ChAdOx1 nCoV-19, although the seropositive rates between both vaccines were similar (2.4- or 3.3-fold higher at the first vaccination; 14.7-fold higher at the second vaccination). Another previous study using Roche Elecsys SARS-CoV-2 total antibody could not be compared directly, but they also demonstrated that BNT162b2 showed higher values and higher fold increase (1.4-fold higher at the first vaccination; 2.2-fold higher at the second vaccination) than ChAdOx1 nCoV-19 ( 18 ). However, a higher value of SARS-CoV-2 antibodies after vaccination should not be considered evidence of a more effective vaccine.…”
Section: Discussionmentioning
confidence: 93%
“…In line with previous studies, the second dose of AZD1222 substantially enhanced the initial antibody response in our cohort 31,66,74 . Therefore, we wanted to investigate the relationship between the antibody levels and the cellular responses elicited by the booster.…”
Section: Discussionsupporting
confidence: 93%
“…We demonstrated this in a strictly standardized study setting concerning the time of blood collection and the vaccine used: three weeks after the first dose of BNT162b2. It was expected and has already been shown that antibody responses are dependent on the type of vaccine used 30,31 . Moreover, time kinetics of post-vaccination antibody levels have been described for different vaccines and various antibody assays 17,3237 .…”
Section: Introductionmentioning
confidence: 95%
“…We could previously show that reporting standardized binding antibody units (BAU/mL) is insufficient for different test systems to provide numerically comparable results ( 16 ). Moreover, antibody responses are dependent on the type of vaccine used ( 18 , 19 ). In this view, the temporal kinetics of antibody levels after vaccination were described for different vaccines and different antibody assays ( 20 23 ).…”
Section: Introductionmentioning
confidence: 99%